Strategi Komunikasi Keluarga dalam Mengatasi Stress Belajar Online Anak Masa Pandemi Covid-19 di Desa Sei Rotan - Muya Syaroh Iwanda lubis; Cut Alma Nuraflah; Azizah Hanum (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Communication has an important role in every family especially. Imagine what happens when in a family far from the word communication, of course misunderstandings will continue to occur. Because there is no good communication between each other. Family communication exists to provide order and help overcome stress levels in children, especially in doing online learning at home after the Covid-19 pandemic. Where the child also feels that his freedom in learning is limited without any friends in class. Information provided if this online learning period will be permanent. This is certainly homework for parents in dealing with stress on children. The Technology Readiness Level (TKT) in this study is expected that parents can receive suggestions from the author to make alternative learning at home by bringing some of their friends, teaching parents to use video call technology in the learning process with the child's teacher and school friends, if all this time learn only to use WA (whatsapp) only. This research was conducted in Si Rotan Village, to be precise Dusun I and Dusun II, because in these areas there are more than other hamlets. From the research conducted it shows that the role of family communication in overcoming the stress of online learning can be done well by parents.